2017
DOI: 10.1039/c7bm00431a
|View full text |Cite
|
Sign up to set email alerts
|

MRI-guided tumor chemo-photodynamic therapy with Gd/Pt bifunctionalized porphyrin

Abstract: Porphyrin derivatives have been widely applied in MR imaging and photodynamic cancer therapy. We here report a novel Gd/Pt bifunctionalized porphyrin derivative (Gd/Pt-P1) for MRI-guided chemo-photodynamic cancer therapy. Gd/Pt-P1 was prepared from tetra(4-pyridyl) porphyrin (P1) via step by step coordination to cisplatin and gadolinium (Gd(iii)). Gd/Pt-P1 showed a particularly high synergetic chemo-photodynamic antitumor effect in vivo with a tumor inhibition rate (TIR) of 96.6% and excellent MR imaging perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…32,33 The primary modality for imaging tumors is MRI, which allows for whole body, noninvasive imaging with excellent so tissue contrast and spatial resolution. [32][33][34][35][36] While a few examples of Gd(III)-Pt(II) theranostics have appeared, [37][38][39] to our knowledge there are no reported examples of Pt(IV) prodrugs containing a Gd(III) complex for contrast-enhanced MR imaging either in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 The primary modality for imaging tumors is MRI, which allows for whole body, noninvasive imaging with excellent so tissue contrast and spatial resolution. [32][33][34][35][36] While a few examples of Gd(III)-Pt(II) theranostics have appeared, [37][38][39] to our knowledge there are no reported examples of Pt(IV) prodrugs containing a Gd(III) complex for contrast-enhanced MR imaging either in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate tumor death was observed and this study indicated the need to optimize different parameters such as drug dose and light application. A porphyrin-based PS linked to chemotoxic platinum(II) complexes and incorporating a gadolinium(III) ion has been reported for tumor treatment by PDT and chemotherapy and for MR imaging [49]. It has been obtained from a 5,10,15,20-tetra(4-pyridyl)-porphyrin (P1) that is coordinated to four Pt(II) complexes (Pt-P1) and to one Gd(III) ion (Gd/Pt-P1) (Figure 4a).…”
Section: Molecular Theranostic Agents With Combined Pdt and Mri Studiesmentioning
confidence: 99%
“…In order to obtain contrast agents with high relaxivity at high magnetic fields, the strategy of increasing the number of coordinated water molecules at the Gd(III) center is particularly appealing as this allows for the almost doubling of the r1 relaxivity value independently of the magnetic field. In this case, careful design of hepta-or hexadentate ligands is necessary in order to obtain Gd(III) complexes with good thermodynamic stability and kinetic inertness, and to avoid ternary complex A porphyrin-based PS linked to chemotoxic platinum(II) complexes and incorporating a gadolinium(III) ion has been reported for tumor treatment by PDT and chemotherapy and for MR imaging [49]. It has been obtained from a 5,10,15,20-tetra(4-pyridyl)-porphyrin (P1) that is coordinated to four Pt(II) complexes (Pt-P1) and to one Gd(III) ion (Gd/Pt-P1) (Figure 4a).…”
Section: Molecular Theranostic Agents With Combined Pdt and Mri Studiesmentioning
confidence: 99%
“…

with subsequent damage to the cell components and consequent cell death. [2][3][4][5] However, despite the great potential of porphyrins as photosensitizers, these compounds possess crucial limitations in terms of biomedical application [6,7] such as a high dark toxicity, rather low activity under physiological conditions and typically poor water solubility. To optimize cell damage in the tumor and prevent significant collateral damage to healthy cells, the PS should be specifically localized in the pathogenic region.

…”
mentioning
confidence: 99%
“…[2][3][4][5] However, despite the great potential of porphyrins as photosensitizers, these compounds possess crucial limitations in terms of biomedical application [6,7] such as a high dark toxicity, rather low activity under physiological conditions and typically poor water solubility. [2][3][4][5] However, despite the great potential of porphyrins as photosensitizers, these compounds possess crucial limitations in terms of biomedical application [6,7] such as a high dark toxicity, rather low activity under physiological conditions and typically poor water solubility.…”
mentioning
confidence: 99%